Cyclotron Frequency Oscillations in Semiconductor Plasma in Modulated Magnetic Field - Jankauskas, Z.; Kvedaras, V. (Elektronika ir Elektrotechnika, 2009)
Radio frequency magnetoplasmic waves known as helicons will propagate in solid-state plasma of semiconductors when a strong magnetic field is applied. Helicons have an exact analogy with a electromagnetic whistler wave which is frequently propagated in the rarefied plasma of the Earth’s ionosphere. In our experiments the modulated magnetic field is being used for excitation of helicons. Physically it means that the semiconductor conductivity and effective dielectrical constant are modulated with the same cyclotron frequency of infrared range. The semiconductor sample is in the form of plae and magnetic field is perpendicular to the surface of the plate. It is shown that in the case of modulated field along with the RF helicon waves the transient cyclotron frequency oscillations exist in the semiconductor plasma. For observation of the cyclotron radiation frequency c the modulation depth about one percent is sufficient. The measurement of c provides an opportunity to determine the masses of electrons and holes in solid-state plasma of semiconductors. The proposed method can be used in the cases of pulse and sinusoidal modulation of the magnetic field. Bibl. 5 (in English; summaries in English, Russian and Lithuanian).